2013
DOI: 10.1007/s11249-013-0244-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Frictional Resistance of a Capsule Robot Moving in the Intestine at a Constant Velocity

Abstract: Capsule robot is the direction for future development of capsule endoscopy. The imperfection of friction model between the capsule robot and the intestine has been one of the biggest obstacles of its development. Uniform motion is the main mode of the capsule robot in the intestine. However, the frictional resistance variation of the capsule robot in this period has not been understood completely until now. This is the research content in the paper. First, some experiments are conducted to measure actual frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Others have developed models for predicting the resistance force on a capsule in the bowel [22,[24][25][26]29], and they all rely on the assumption that the capsule distends the bowel in the radial direction, allowing for a hoop stress analysis. However, this assumption is not valid for a colonoscopy with insufflation or any other procedure where a cylindrical-shaped device is in one-sided contact with tissue (e.g., insufflated GI or abdominal wall).…”
Section: Theory: Analytical Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have developed models for predicting the resistance force on a capsule in the bowel [22,[24][25][26]29], and they all rely on the assumption that the capsule distends the bowel in the radial direction, allowing for a hoop stress analysis. However, this assumption is not valid for a colonoscopy with insufflation or any other procedure where a cylindrical-shaped device is in one-sided contact with tissue (e.g., insufflated GI or abdominal wall).…”
Section: Theory: Analytical Model Developmentmentioning
confidence: 99%
“…Others have extensively studied the effect of capsule diameter, length, speed, normal force, and velocity, all of which were studied to assess model validity in this work. In summary, literature reports that resistance force is directly proportional to capsule speed [21][22][23][24][25][26][27][28][29], diameter [20-24, 29, 30], length [23,29,30], and normal force [21,23,31].…”
Section: Introductionmentioning
confidence: 99%
“…My previous work also shows the same result [25,26,27], and we analyzed the friction resistance of CR at stage of start, stop and uniform motion [28]. It is found that the friction exhibits fluctuating change when CR moves at a constant velocity, which has a great significance for the control strategy of CR [29]. But the absence of analytical model results in that it cannot be used directly.…”
Section: Introductionmentioning
confidence: 65%
“…The COF for the small intestine in contact with another 13 Repetitive experimental data at 10 mm/s [29] surface is highly variable and depends upon the surface material, region of intestine, contact area and animal [33]. The surface material is PDMS, and the experiment object is laboratory pig in my work.…”
Section: Influence Of Cofmentioning
confidence: 99%
See 1 more Smart Citation